PHYTOHAEMAGGLUTININ’S EFFECT ON NEOSPORA CANINUM ANTIGEN PRODUCTION - Kikuti, Mariana; Richini-Pereira, Virgínia Bodelão; da Silva, Rodrigo Costa; Langoni, Helio (Archives of Veterinary Science, 2013)
The parasite Neospora caninum affects mainly cattle and dogs. This study aimed to evaluate the effect of phytohaemagglutinin (PHE) in antigen production of N. caninum NC-1 strain in gerbils (Meriones unguiculatus) and in vitro. 20 gerbils were used, 10 inoculated intraperitoneally with 1 x 106 tachyzoites and 10 with 1 x 106 tachyzoites plus 300 µL/mL of PHE. 16 bottles of Vero cell culture were inoculated, 8 with 1.5 x 105 tachyzoites and 8 with 1.5 x 105 tachyzoites plus 30 µL/mL of PHE. Serology of gerbils was performed on day 0 and before euthanasia. Tachyzoites present in peritoneal fluid and cell culture bottles were quantified by Neubauer chamber and by real-time PCR (qPCR). PHE has not interfered in the production of tachyzoites of N. caninum in intraperitoneal inoculated gerbils and the effect of PHE in cell culture had a negative impact, considering the qPCR technique as the gold standard.